2015
DOI: 10.1002/acr.22475
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Birth Weight and Preterm Birth With the Incidence of Knee and Hip Arthroplasty for Osteoarthritis

Abstract: Objective. Low birth weight (LBW) and preterm birth have been associated with adverse adult outcomes, including hypertension, insulin resistance, cardiovascular disease, and reduced bone mass. It is unknown whether LBW and preterm birth affect the risk of osteoarthritis (OA). This study aims to examine whether LBW and preterm birth were associated with the incidence of knee and hip arthroplasty for OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…In the Danish working population, cumulative lifting was modestly associated with total hip replacement in men, as was high BMI at age 25 years and gain in BMI in both men and women (56). In the Australian Diabetes, Obesity and Lifestyle Study, low birth weight and preterm birth were associated with total hip replacement in adult life (57). In patients scheduled to undergo total hip replacement in a U.S. study, hip pain was associated with self-report and performance measures of function, while hip abduction strength was associated only with performance measures (58).…”
Section: Resultsmentioning
confidence: 99%
“…In the Danish working population, cumulative lifting was modestly associated with total hip replacement in men, as was high BMI at age 25 years and gain in BMI in both men and women (56). In the Australian Diabetes, Obesity and Lifestyle Study, low birth weight and preterm birth were associated with total hip replacement in adult life (57). In patients scheduled to undergo total hip replacement in a U.S. study, hip pain was associated with self-report and performance measures of function, while hip abduction strength was associated only with performance measures (58).…”
Section: Resultsmentioning
confidence: 99%
“…The highest risk for hand OA was observed in those who had been heaviest at age 53 years and lightest at birth [ 18 ]. However, studies reported that birth weight did not appear to be a major influence on the later development of knee OA in women [ 19 ] and the general population [ 20 ] after accounting for other confounding factors, including obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 provides an overview of the included studies. The included studies comprised two cohort [ 32 , 34 ], one case-control [ 35 ], and two cross-sectional studies [ 36 , 37 ] published between 1993 and 2015. Two studies originated from Australia [ 32 , 35 ], two from the UK [ 34 , 36 ], and one from Turkey [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hip bone abnormality included self-reported DDH [ 35 ], α-angle of the hip joint (suggestive of immature or pathologic hip) by ultrasound examination [ 37 ], and hip deformity by footprint angle and hip rotation [ 36 ]. Hip OA was defined by American College of Rheumatology (ACR) algorithms based on the presence of osteophytes and overall Kellgren and Lawrence (K-L) score assessed from hip radiographs [ 34 ], and hip arthroplasty for OA [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation